Systematic literature review: risiko privasi dan keamanan data pribadi dalam penggunaan artificial intelligence (AI) - Ardi, Mohamad; Bintari, Evi Dianti (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2024)
The advancement of sophisticated technology is followed by the development of an increasingly modern era. Various kinds of technology have been created, one of which is Artificial Intelligence (AI) which has helped human life in carrying out activities in the fields of telecommunications, transportation, health, and even defense and security. AI requires access to personal data which is later processed and analyzed by the technology. Among the data collected, there is sensitive data, namely personal data that is vulnerable to being tampered with, stolen, and manipulated. The purpose of this research is to know and understand the various privacy and security risks of personal data in the use of AI that often occur along with solutions to prevent them. This research applied the Systematic Literature Review (SLR) method. Based on the SLR results, researchers found 200 Scopus journal articles in the search using Publish or Perish 8 and the help of other applications such as Zotero, Mendeley, VOSviewer, and Microsoft Excel which were then filtered into 59 selected articles to be analyzed descriptively. The results showed that AI easily obtained personal data from users of the technology. Understanding the occurrence of data collection by AI due to the transmission of data by individuals through various platforms is the most important element in ensuring personal data security. The conclusion of this research is the need for a holistic understanding in ensuring personal data security. Cooperation between technology companies, society and the government is needed to ensure access to personal data taken by AI is not misused and certainty in personal data security.